1975
DOI: 10.1002/1097-0142(197507)36:1<129::aid-cncr2820360109>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Heparin and chemotherapy in the management of inoperable lung carcinoma

Abstract: Twenty-eight patients with inoperable or metastatic carcinoma of the lung who failed to respond to conventional chemotherapy and/or radiotherapy were entered in this study. All of them received repeated courses of multiple chemotherapy (cyclophosphamide, 5-fluorouracil, 6-thioguanine, methotrex-ate, and vincristine) with o r without concurrent intravenous heparin an-ticoagulation. No tumor regression was noted in any of the 14 patients who received the multiple chemotherapy only. On the contrary, tumor progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…These studies frequently focus on heparin, as an anticoagulant. Studies have demonstrated regression in the primary tumor [17, 18], as well as a reduced likelihood of developing metastases [19]. …”
Section: Discussionmentioning
confidence: 99%
“…These studies frequently focus on heparin, as an anticoagulant. Studies have demonstrated regression in the primary tumor [17, 18], as well as a reduced likelihood of developing metastases [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Elias et al (83) showed that tumors respond to the combined use of heparin with cytotoxic agents in a small group of cancer patients and that tumor regression could be observed in the patients with highly resistant cancers to that of chemotherapy alone. Edlis et al (84) reported an objective response in only one of 19 patients with lung cancer treated with heparin and cyclophosphamide.…”
Section: Application Of Anticoagulants Fibrinolytic or Antiplateletmentioning
confidence: 99%
“…Due to their anticoagulant function, they can inhibit thrombin and fibrin formation induced by cancer cells, and therefore, heparins may potentially inhibit intravascular arrest of cancer cells and thus affects metastasis. However, some evidence shows that the anticoagulant properties of heparin is not the only way this molecule affects cancer progression, since heparin may modify gene expression, induce apoptosis [8][9][10] or differentiation [11] and inhibit drug resistance [12] in some cancer cells.…”
Section: Introductionmentioning
confidence: 99%